Answer:
(x - 3)(x - 9)
Step-by-step explanation:
Consider the factors of the constant term (+ 27) which sum to give the coefficient of the x- term (- 12)
The factors are - 3 and - 9, hence
x² - 12x + 27 = (x - 3)(x - 9 )
Answer:
8
Step-by-step explanation:
Cress to the person below me that’s who I got anwser from hah
0.01 that should be your answer
Answer:
..
Step-by-step explanation:
Answer:
x=3
Step-by-step explanation:
-8x - 1= -25
Add 1 to each side
-8x-1+1 = -25+1
-8x = -24
Divide each side by -8
-8x/-8 = -24/-8
x = 3